Design and fabricate Mosfet Masks at KUKUM Microfabrication Cleanroom for teaching undergraduates - Mohd Zainizan, Sahdan; Uda, Hashim; Hashim, Saim; Marlia, Morsin (Kolej Universiti Kejuruteraan Utara Malaysia, 2009)
Organized by Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 18th - 19th May 2005 at Putra Palace Hotel, Kangar.